A BIBLIOMETRIC ANALYSIS OF SUSTAINABLE MULTILINGUALISM: INSIGHTS FROM 25 ISSUES (2012–2024) - Çelik, Servet; Daukšaitė-Kolpakovienė, Aurelija (Sustainable Multilingualism / Darnioji daugiakalbystė, 2025)
As an outlet in the field of multilingual studies, Sustainable Multilingualism (ISSN: 2335-2019; eISSN: 2335-2027) has contributed significantly to research on language diversity, education, and policy. Since its establishment in 2012, the journal has provided a platform for scholarship that addresses the complex dynamics of multilingualism in both local and global contexts. This bibliometric study examines the first 25 volumes of Sustainable Multilingualism (2012–2024) to evaluate its thematic evolution, authorship patterns, institutional and geographic reach, and citation performance. The corpus comprises 249 peer-reviewed research articles, which were analyzed using manual coding and bibliometric tools, including Excel and VOSviewer. The findings reveal that annual article output stabilized at ten per issue after 2016, reflecting consistent editorial capacity. Thematically, early volumes focused on identity, language policy, and rights, while more recent issues highlight digital multilingualism, English as a Medium of Instruction (EMI), and artificial intelligence in education. Lithuania, Türkiye, Latvia, Spain, and Poland emerge as leading contributors, with author affiliations spanning more than 40 countries. However, contributions remain unevenly distributed, with a strong European concentration and limited or no participation from the Middle East (excluding Türkiye and Iran), Oceania, Southeast Asia, South Asia, East Asia, Africa, South America, the Caribbean, and Central Asia. Citation metrics demonstrate a modest but growing impact: the journal’s CiteScore increased to 0.9 in 2024, its SCImago Journal Rank (SJR) rose to 0.211, and its h5-index reached 10, reflecting a steady integration into global scholarly discourse. Frequently cited and downloaded articles highlight the journal’s impact on multilingual education, migration studies, and research on endangered languages. The study concludes that while Sustainable Multilingualism has achieved international visibility and sustained scholarly contributions, expanding representation to include underrepresented regions would enhance diversity and further increase global engagement. Building on the findings, some recommendations are also included to guide the journal’s editorial strategy and future growth.